The Influence of Work Facilities on Employee Performance at the Regional Financial Management Agency Secretariat Section of South Sulawesi Province - Nurul Jihan Pratiwi; Jamaluddin Jamaluddin; Risma Niswaty; Rudi Salam (Jurnal Ad'ministrare, 2019)
Adequate work facilities with suitable conditions that are well maintained and will help smooth the work process in an organization. This study aims to determine the use of work facilities, on the performance of employees in the section of the Regional Financial Management Agency Secretariat of South Sulawesi Province. Therefore, to achieve these objectives researchers used data collection techniques with observation, questionnaires, and documentation with a population of 35 people. While the data analysis techniques used are descriptive statistical analysis using percentages and for inferential statistical analysis techniques using data normality tests, product moment correlation analysis, and simple linear regression analysis. The results of the study indicate that the work facilities in the section of the South Sulawesi Provincial Financial Management Agency Secretariat are in a good category, in terms of indicators: machinery and equipment, infrastructure, work equipment, land, and buildings. For the quality of employee performance in the section of the South Sulawesi Provincial Financial Management Agency Secretariat in a good category, which is viewed from: quality, quantity, timeliness, effectiveness, and independence. Based on the product moment correlation test analysis, there is a positive and significant influence on the use of work facilities on the performance of employees in the section of the Regional Financial Management Agency of South Sulawesi Province at 17.00%, stated to be accepted with a moderate level of influence. From the results of simple linear regression analysis shows that there is an influence of work facilities on employee performance in the section of the Regional Financial Management Agency Secretariat of South Sulawesi Province.